2009
DOI: 10.1253/circj.cj-09-0260
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Endocardial Focal Discharges During Ventricular Fibrillation With Prolonged Global Ischemia in Isolated Rabbit Hearts

Abstract: Background: Ventricular fibrillation (VF) during prolonged (>5 min) global ischemia (GI) could be due to repetitive endocardial focal discharges (REFDs). This hypothesis was tested in isolated rabbit hearts. Methods and Results: With optical mapping, simultaneous endocardial (left ventricle, LV) and epicardial (both ventricles) activations during VF with prolonged GI were studied (protocol I, 8 hearts). Lugol solution was applied to the LV endocardium in additional 5 hearts after 5-min GI (protocol II). During… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
26
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(33 citation statements)
references
References 27 publications
7
26
0
Order By: Relevance
“…However, we previously demonstrated that after endocardial and midmyocardial ablation, the epicardial cells have an intrinsic ability to generate H 2 O 2 -induced EADs, triggered activity, and VF (6). However, we can not dismiss the potential role of the endocardial Purkinje fiber network in the initiation and maintenance of focal VF (30,31). It could be argued that the observed epicardial focal mechanism may result from micro–re-entry, rather than triggered foci (32).…”
Section: Discussionmentioning
confidence: 93%
“…However, we previously demonstrated that after endocardial and midmyocardial ablation, the epicardial cells have an intrinsic ability to generate H 2 O 2 -induced EADs, triggered activity, and VF (6). However, we can not dismiss the potential role of the endocardial Purkinje fiber network in the initiation and maintenance of focal VF (30,31). It could be argued that the observed epicardial focal mechanism may result from micro–re-entry, rather than triggered foci (32).…”
Section: Discussionmentioning
confidence: 93%
“…The ascending aorta was cannulated and perfused with 37°C Tyrode's solution composed of (in mmol/L): 125 NaCl, 4.5 KCl, 0.5 MgCl2, 24 NaHCO3, 1.8 NaH2PO4, 1.8 CaCl2, 5.5 glucose, and albumin (40 mg/L), respectively. 6,18, 19 Coronary perfusion pressure and flow rate were 60-65 mmHg and 35-45 ml/min, respectively. 6 The hearts were perfused and superfused in a thermostatically controlled tissue bath.…”
Section: Langendorff Preparation Of Isolated Rabbit Heartsmentioning
confidence: 93%
“…In those days, because detailed analysis of activation in the ventricles was not available, the difference between electrically induced VF and ischemia-related spontaneous VF was unknown. Based on the observations in the study by Wu et al, 12 repetitive endocardial focal discharges during VF offer an attractive reason for the observations by Ouyang et al…”
Section: Article P 1803mentioning
confidence: 92%
“…In those days, because detailed analysis of activation in the ventricles was not available, the difference between electrically induced VF and ischemia-related spontaneous VF was unknown. Based on the observations in the study by Wu et al, 12 repetitive endocardial focal discharges during VF offer an attractive reason for the observations by Ouyang et alBecause many clinical studies have shown that electrical activity originating from the pulmonary veins causes atrial fibrillation, isolation of these veins has become a rational and efficient strategy to cure atrial fibrillation. While repetitive firing in the pulmonary veins activates the atria, activa-…”
mentioning
confidence: 99%